Occlusion of regulatory sequences by promoter nucleosomes in vivo. - Changhui Mao; Christopher R Brown; Joachim Griesenbeck; Hinrich Boeger (PLoS ONE, 2011)
Nucleosomes are believed to inhibit DNA binding by transcription factors. Theoretical attempts to understand the significance of nucleosomes in gene expression and regulation are based upon this assumption. However, nucleosomal inhibition of transcription factor binding to DNA is not complete. Rather, access to nucleosomal DNA depends on a number of factors, including the stereochemistry of transcription factor-DNA interaction, the in vivo kinetics of thermal fluctuations in nucleosome structure, and the intracellular concentration of the transcription factor. In vitro binding studies must therefore be complemented with in vivo measurements. The inducible PHO5 promoter of yeast has played a prominent role in this discussion. It bears two binding sites for the transcriptional activator Pho4, which at the repressed promoter are positioned within a nucleosome and in the linker region between two nucleosomes, respectively. Earlier studies suggested that the nucleosomal binding site is inaccessible to Pho4 binding in the absence of chromatin remodeling. However, this notion has been challenged by several recent reports. We therefore have reanalyzed transcription factor binding to the PHO5 promoter in vivo, using 'chromatin endogenous cleavage' (ChEC). Our results unambiguously demonstrate that nucleosomes effectively interfere with the binding of Pho4 and other critical transcription factors to regulatory sequences of the PHO5 promoter. Our data furthermore suggest that Pho4 recruits the TATA box binding protein to the PHO5 promoter.